Comparison of Pearl Sac Formation in Four Mussel Species (Mollusca: Bivalvia: Unionoida) at the Graft Implantation - Hülya Şereflişan (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the most suitable mantle part and host mussel species for pearl sac formation were determined. A total of 400 mussels, consisting of four different types (Unio terminalis, Potamida littoralis, Leguminaia wheatleyi and Anodonta pseudodopsis) were used. The average dorso-ventral lengths of the mussels were respectively; 7.89±0.25; 7.28±0.38; 10.68±0.27 and 11.14±0.34 cm. Mantle tissue slices in the size of 3×3 mm obtained from the pallial edge of mantle tissue were used as grafts. Two different mantle sections were identified for graft implantation, one being the mantle cavity and the other was incisions on the mantle tissue. At the end of the three-month pearl culture, the mantle cavity section was identified as the best graft implant site. U. terminalis was determined as the most successful species in terms of survival rate and pearl formation. P. littoralis was the second successful species and L. wheatleyi was the lowest among the species. This study is a guide for long-term pearl production on nacre thickness and quality which are considered important in pearl production.